Comparison of the mean of the first two blood pressure readings with the overall mean of three readings on a single occasion. Issue 4 (22nd April 2022) - Xu, Shao-Kun; Chen, Xin; Sheng, Chang-Sheng; Cheng, Yi-Bang; Wang, Hong-Yu; Yu, Wei; Li, Yan; Wang, Ji-Guang
Abstract : Objective: Guidelines differed on the required number of blood pressure (BP) readings for accurate BP assessment. We, therefore, compared the mean of the first two BP readings with the overall mean of three readings in the diagnosis of hypertension. Methods: BP was measured three times consecutively with a 1 min interval using a validated automated electronic BP monitor in volunteers aged at least 18 years. The mean of the first and second BP readings was compared with the mean of the three blood pressure readings for the diagnostic accuracy of hypertension. Results: Of the 77 520 study participants, 65.2 and 25.2% had a SBP or DBP difference at least 5 mmHg and at least 10 mmHg between the first and second BP readings, respectively. Regardless whether the BP difference between the first two BP readings was at least 5 mmHg or at least 10 mmHg for systolic and diastolic alone or both, significant ( P  < 0.0001) SBP/DBP differences between the mean of the first two BP readings and the overall mean of three readings were observed with an absolute value up to 1.28/1.11 mmHg. However, the mean of the first two BP readings exhibited good reliability and sufficient agreement in the diagnosis of hypertension with a kappa statistic at least 0.88, except that the difference between the first and second BP readings was at least 10 mmHg for both systolic and diastolic ( κ =0.79). The diagnostic accuracy was similar across age quartile, sex, and BP category. Conclusion: Two BP readings may be sufficient, unless the BP difference between the two readings was at least 10 mmHg for both systolic and diastolic.